Development and testing of the CALDs and CLES+T scales for international nursing students' clinical learning environments. (2nd March 2017) - Mikkonen, Kristina; Elo, Satu; Miettunen, Jouko; Saarikoski, Mikko; Kääriäinen, Maria
Abstract: Aim: The purpose of this study was to develop and test the psychometric properties of the new Cultural and Linguistic Diversity scale, which is designed to be used with the newly validated Clinical Learning Environment, Supervision and Nurse Teacher scale for assessing international nursing students' clinical learning environments. Background: In various developed countries, clinical placements are known to present challenges in the professional development of international nursing students. Design: A cross‐sectional survey. Methods: Data were collected from eight Finnish universities of applied sciences offering nursing degree courses taught in English during 2015–2016. All the relevant students ( N  =   664) were invited and 50% chose to participate. Of the total data submitted by the participants, 28% were used for scale validation. The construct validity of the two scales was tested by exploratory factor analysis, while their validity with respect to convergence and discriminability was assessed using Spearman's correlation. Results: Construct validation of the Clinical Learning Environment, Supervision and Nurse Teacher scale yielded an eight‐factor model with 34 items, while validation of the Cultural and Linguistic Diversity scale yielded a five‐factor model with 21 items. Conclusion: A new scale was developed to improve evidence‐based mentorship of international nursing students in clinical learning environments. The instrument will be useful to educators seeking to identify factors that affect the learning of international students.